Badanie poziomu satysfakcji pacjentów z funkcjonowania podstawowej opieki zdrowotnej w Polsce i we Włoszech. Analiza porównawcza = Measuring patient satisfaction in primary health care. Comparative analysis - Aneta Rutkowska; Joanna Skonieczna; Dominik Olejniczak (Kazimierz Wielki University, 2015)
Rutkowska Aneta, Skonieczna Joanna, Olejniczak Dominik. Badanie poziomu satysfakcji pacjentów z funkcjonowania podstawowej opieki zdrowotnej w Polsce i we Włoszech. Analiza porównawcza = Measuring patient satisfaction in primary health care. Comparative analysis. Journal of Education, Health and Sport. 2015;5(10):251-261. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32858 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A251-261 https://pbn.nauka.gov.pl/works/663413 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015.   Badanie poziomu satysfakcji pacjentów z funkcjonowania podstawowej opieki zdrowotnej w Polsce i we Włoszech. Analiza porównawcza Measuring patient satisfaction in primary health care. Comparative analysis   Rutkowska Aneta, Skonieczna Joanna, Olejniczak Dominik   Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny Public Health Department, Medical University of Warsaw   Słowa kluczowe: podstawowa opieka zdrowotna, jakość opieki zdrowotnej, pacjenci. Key words: primary health care, quality of health care, patients.   Streszczenie   Wprowadzenie i cel pracy Jakość i jej poprawa powinny stanowić kluczową rolę w sektorze medycznym. Celem badania była ocena poziomu satysfakcji pacjentów z systemu podstawowej opieki zdrowotnej w Polsce i we Włoszech na podstawie elementów takich jak uzyskiwanie przez pacjenta informacji w procesie leczenia, aspekty estetyczne, czas oczekiwania na wizytę do specjalisty oraz postawy personelu medycznego wobec pacjenta. Materiał i metoda Badanie zostało przeprowadzone w Polsce i we Włoszech w 2012 roku. W badaniu zastosowano metodę sondażu diagnostycznego. Badanie miało charakter anonimowy. Zastosowano dwie wersje ankiet (polską i włoską) złożonych z 25 pytań. Badaniem objęto 200 pełnoletnich osób, 100 osób w Polsce oraz 100 osób we Włoszech. Przedział wiekowy badanych to 18-75 lat. Wyniki Polscy respondenci w większości deklarowali, iż najchętniej korzystają z prywatnego sektora ochrony zdrowia (68%). Większość włoskich respondentów (91%) deklaruje częstsze korzystanie z publicznego sektora ochrony zdrowia. W publicznych placówkach dobrze lub bardzo dobrze kompetencje pracowników oceniło, aż 56% polskich badanych oraz około 62% włoskich respondentów. Około 43% polskich badanych oraz 35% włoskich respondentów pozytywnie oceniło system usług zdrowotnych w swoim kraju. Wnioski Włoska podstawowa opieka zdrowotna prawdopodobnie wymaga działań mających na celu poprawę przepływu informacji pomiędzy personelem medycznym. Należy również rozważyć przeprowadzenie kontroli oceniających realizację prawa pacjenta do informacji. Funkcjonowanie publicznego sektora opieki zdrowotnej w Polsce powoduje niechęć do korzystania z jego usług. Należy rozważyć implementację rozwiązań mających na celu budowanie pozytywnego wizerunku publicznego systemu ochrony zdrowia w Polsce.   Abstract   Introduction and aim Quality and improvement of quality should have a key role in the medical sector. The main aim of the study was to assess the level of patient satisfaction with primary health system in Poland and Italy. There were analysed following parts(elements): obtaining information during the process of medical treatment, aesthetic aspects, waiting time and staff attitudes towards patients. Material and methods The survey was conducted in 2012 in Poland and Italy. In the study a method of diagnostic survey was used. Two versions of the anonymous questionnaires (in Polish and Italian) composed of 25 questions were used. The study included 200 adults, 100 Polish and 100 Italians. The age range was 18-75 years. Results Majority of Polish respondents (68%) declared that mostly they use private health care sector. Respondents from Italy, by contrast reported more frequent use of the public health sector (91%). About 56% of Polish and 62% of Italian participants assessed public health care profesionals competencies as good or very good. About 43% of Polish and 35% of Italian respondents positively evaluated the health service system in their countries. Conclusions Primary health care in Italy likely requires actions to improve the flow of information between medical staff. Carrying out an evaluation of implementation of the patient's right to information should be considered. Functioning of the public health care sector in Poland causes avertion to use its services. Creating a positive image of the public health system in Poland should be consider.